Aplicação de corante natural obtido de extrato em pó da casca de pitaia em sorvete - Rebouças, Cinthia Regina da Silva (2019)
Natural pigments can be obtained from fruit peels and used as an alternative dye in the food industry. Among them, the betalains, found in the pitaya (Hylocereus sp.) peel can be used in ice creams because of their good stability at low temperatures. The objective of this work was to compare the application of the natural dye extracted from the pitaya peel, encapsulated and freeze-dried with the artificial dye (amaranth red) used in the edible ice cream industry. After obtaining the aqueous betalain extract from pitaya peels and distilled water (1:10) using ultrasonic technology (38 minutes of extraction at 30 ° C), it was encapsulated with maltodextrin and inulin by freeze-drying. The physico-chemical parameters of the liquid extract (pH, soluble solids, color, betalain content and water activity) and freeze-dried extract (color, betalain content, moisture, water activity, hygroscopicity, solubility and degree of caking). Three formulations of strawberry flavored ice creams were prepared: without dye, with dye obtained from pitaya peel and with artificial amaranth dye. The processed ice creams were submitted to microbiological analysis (Staphylococcus Coagulase Positive (UFC / g), Thermotolerant Coliforms at 45 ° C and Salmonella spp. in 25 g); physical-chemical (pH, soluble solids and color); and sensory (acceptance - overall impression, color, taste, aroma and texture, preference and purchase intention). The color stability of the ice cream and the obtained powder was evaluated every 30 days for 120 days from the variation of the color coordinates (L *, a *, b *) obtained for each period. Among the results found for characterization of the powder, solubility was 97.92%, considered high in relation to the literature, as well as the degree of caking of 55.93%. During the 120 days of storage, the powder presented a great variation of the color coordinate L, indicating its darkening, probably due to the humidity acquired along the storage. The results for the overall impression, color and purchase intention of the ice cream showed a significant difference (p <0.05) between sample without dye and the others, demonstrating the importance of the addition of color for product acceptance. In the preference ordering test, there was no significant difference between the samples with addition of the dyes. The ice cream had no significant color variation (p <0.05) during storage of 120 days. It is concluded that the extract obtained from the bark of the pitaya has potential use for the industry of ice cream, being able to replace with success the artificial dye of pink coloration.